Mechanism and Theory in Food Chemistry, Second Edition - Wong, Dominic W.S (Springer International Publishing, 2018)
For the first time in over twenty-five years, this unique and popular textbook on food chemistry mechanism and theory has received a full update. Emphasizing the underlying chemical reactions and interactions that occur in foods during processing and storage, this book unifies the themes of "what", "how" and "why" in the language of equations, reactions and mechanisms. This book is the only work which provides in-depth focus on aspects of reaction mechanisms and theories in the chemistry of food and food systems. With more than 500 chemical equations and figures, this book provides unusual clarity and relevance, and fills a significant gap in food chemistry literature. It is a definitive source to consult regarding the important mechanisms that make food components and reactions tick. Mechanism and Theory in Food Chemistry has been a popular resource for students and researchers alike since its publication in 1989. This important new edition contains updates on the original text encompassing a quarter century of advances in food chemistry. Many parts of the original chapters are revised to make for smoother navigation through the subjects, to better explain the underlying chemistry concepts and to fulfill the need of adding topics of emerging importance. New sections on fatty acids, lipid oxidation, meat, milk, soybean and wheat proteins, starch and many more have been incorporated throughout the revision. This updated edition provides an excellent source of all the important chemical mechanisms and theories involved with food science.